Using Email in Second Language Learning and Teaching - Almashham, Amal Abdullah Ali (Journal of Humanities & Social Sciences, 2018)
This study aims to investigate the impact of using email as one of the most important application in the second language learning. In this study the researcher discussed the benefits of using email in learning the second language according to some previous studies which were done in the same field. She found that the email can improve the students’ language and enhance their learning in two different aspects : inside and outside the class room especially in the writing skills. Also she mentioned to the positive and the negative effects of using email for second language’s learners . So, the teachers can take the benefits of using this application in their teaching and the researchers also can follow the recommendation which the author listed at the end. Finally, I hope this study makes changes in the students’ motivations for enhancing their learning of second language.